The Genera Dyschoriste, Eranthemum and Phaulopsis (Acanthaceae) from Thailand - Kladwong, Pornchai; Chantaranothai, Pranom (Tropical Natural History, 2022)
The synopsis of three genera, Dyschoriste, Eranthemum and Phaulopsis of the family Acanthaceae in Thailand is presented. One species each for Dyschoriste and Phaulopsis is recorded such as Dy. nagchana and P. dorsiflora. Five species in Eranthemum, namely E. burmanicum, E. ciliatum, E. decumbens, E. macrophyllum and E. tetragonum are enumerated. Eranthemum burmanicum and E. macrophyllum are new records from Thailand. Eranthemum obovatum is presently reduced as synonymy under E. tetragonum. Daedalacanthus parishii, D. ciliatus, E. macrophyllum, E. obovatum and E. tetragonum are lectotypified.